FORMULATION AND EVALUATION OF TELMISARTAN SOLID DISPERSIONS USING ENTADA SCANDENS SEED STARCH AND POLOXAMER-188 AS SUPERDISINTEGRANTS - Mannem, Venkatarao; Suryadevara, Vidyadhara; Doppalapudi, Sandeep (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The current research focuses on solubility enhancement of poorly water-soluble drug telmisartan, using novel superdisintegrants such as Entada scandens seed starch and Poloxamer-188. Starches yielded from plants are pharmaceutically useful as binders, diluents, disintegrants, and lubricants. Methods: Starches were extracted from E. scandens seed powder using alkali method (sodium hydroxide at 0.1%, 0.25%, and 0.5% concentrations) and water. These starches were subjected for the evaluation of various physicochemical properties and phytochemical tests. Results: The phytochemical tests revealed the presence of only starch in all the extracts. Of all the starches, the starch prepared from 0.5% sodium hydroxide (ESS4) showed best physicochemical properties. Solid dispersions were prepared using telmisartan, poloxamer-188, and starch (ESS4) in various concentrations using fusion technique. Various pre-formulation parameters were evaluated. From in vitro dissolution studies, it was observed that the solid dispersion formulation TP7 containing telmisartan and poloxamer-188 in 1:4 ratios showed better dissolution rate. Solid dispersion TPS7 containing TP7 formulation and 15% w/w of alkali extracted starch showed faster disintegration and enhanced dissolution rate than the solid dispersions prepared alone with poloxamer-188. Fourier transform infrared spectroscopy and differential scanning calorimetric studies for optimized formulations revealed that there were no major interactions between the drug and excipients. X-ray diffraction studies revealed the crystalline and amorphous nature of formulations. Conclusion: Thus, the solid dispersions prepared using E. scandens seed starch revealed the superdisintegrant property of starch. Â